FAKTOR DETERMINAN KEJADIAN GANGGUAN AKIBAT KEKURANGAN YODIUM (GAKY) PADA IBU HAMIL DI KABUPATEN ENDE FLORES PROPINSI NUSA TENGGARA TIMUR - , Yohanes Don Bosko Demu ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Background: IDD is a major nutrition problem facing the Indonesian government. It may occur to everybody at every stage of life, from prenatal to elderly period. Iodine deficiency is formerly known as goitrogenic, a symptom cased by lack of iodine. Iodine deficiency cannot only cause the swelling of goitre glands but also affect wider aspects. The result of TGR 2003 shows the prevalence of IDD at District of Ende was 22.6%. Objective: To identify factors determining the prevalence of IDD in pregnant mothers at District of Ende Flores Province of Nusa Tenggara Timur. Method: The study was observational with case control study design. It was carried out from January to March 2011 at Subdistrict of Detusoko and Wolowaru, District of Ende Flores Province of Nusa Tenggara Timur involving population of as many as 142 pregnant mothers. Samples consisted of 110 individuals taken using screening system. Research instruments were Food Frequency Questionnaires, Dietary History Method and recall 24 hours. Result: The result of statistical analysis showed the prevalence of TGR in pregnant mothers was 35.45%. Out of five variables observed (intake of iodine, goitrogenics, exposure to pesticide, contraception, E. coli bacillus) three had significant association with the prevalence of TGR (p<0.05)